Case report of neurobrucellosis: a rare complication and neuroimaging findings of a common disease - Zhang, Yu; Zou, Xiao-Yi; Liu, Ling (Frontiers in Immunology, 2025)
Background and objectiveNeurobrucellosis is a rare neurological disorder characterized by diverse clinical manifestations. Although several relevant cases were reported, our understanding of this disorder is limited. In this study, we presented the clinical and imaging characteristics of four cases of neurobrucellosis.MethodsFour patients with neurobrucellosis were diagnosed and treated in the West China Hospital of Sichuan University and Chengdu Shangjin Nanfu Hospital, from January 2020 to September 2023. Data on demographics, clinical phenotypes and symptoms, cerebrospinal fluid investigations, radiological investigations, and therapies were collected and reviewed. This study was approved by and conducted in accordance with the recommendations of West China Hospital’s ethics -.1clinical manifestations of neurobrucellosis in these patients included meningitis, meningoencephalitis, encephalitis, cranial neuropathy, intracranial hypertension, radiculitis, peripheral neuropathy, myelitis, and other psychiatric symptoms. Brucella species were isolated from blood or cerebrospinal fluid (CSF) in four patients; three patients had elevated CSF protein levels, and two had elevated CSF leukocyte counts. All four patients had abnormal imaging findings, including meningeal signs, abnormal cortex and subcortical white matter signals, and signal abnormalities in the vertebral body and spinal cord. All patients were treated with rifampicin (450 mg once daily) and minocycline (100 mg twice daily) for at least 12 weeks, and their clinical symptoms showed significant improvements.ConclusionThis report reviews four cases of neurobrucellosis. All four patients had headache, fever, seizure, cranial nerve damage, low back pain, along with imaging abnormalities, and were successfully treated with antibiotics. The symptoms of neurobrucellosis can be insidious, mild, and non-specific, characterized by various clinical manifestations and atypical imaging findings. This complexity increases the risk of misdiagnosis and missed diagnosis; thus, careful identification, extended treatment, and close follow-up are required.